ARTI DAN BENTUK BUSANA KARNAVAL DALAM PAMERAN “JOGJA FASHION WEEK” DI YOGJAKARTA TAHUN 2007 – 2014 - Amalia, Ita; Helmiana, Atik (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
One of the goals of the Jogja Fashion Week Carnival Fashion Exhibition is to advance the fashion industry in Indonesia, as well as to reduce the number of foreign clothing imports in order to increase the selling value of traditional fabrics in Indonesia and to foster a love for Indonesian products among the general public. local. Fashion exhibitions were quite successful in presenting traditional local products throughout a seven-year period (2007–2014). This study was carried out to determine the classification of fashion trends using an art history approach, as well as to analyze the meaning and social interaction of the community using a sociological approach to art. The carnival fashion style's finale reveals numerous meanings, including fabric imagery, designer, and trademark. Physical and non-physical clothes are the two types of clothing. The style, structure, and aesthetic appearance all reveal the actual form. While the concept of manufacture, social conditions, and history can all be understood as non-physical. Several elements influence the creation of carnival costumes, including social situations involving folklore, fairy tales, and mythology. Carnival dress also emphasizes a comfortable construction, modesty, and the purpose of the garment. Designers are still involved in the